Efficient Use of Energy Resources on Malaysian Farms - Chankoson, Thitinan; Jermsittiparsert, Kittisak; Wareewanich, Thitinant (International Journal of Energy Economics and Policy, 2020)
The purpose of this study is to discover an approach where the outputs of the farms are maximum at the minimal input. Malaysia is well known for its crop (such as rubber, rice, palm oil, tea). Prior studies show that due to the climate change, there are likely chances that the farms of Malaysia will go extinct. In this study, the main focus is to efficiently use the energy resources to save it for the future in a prolonged manner. The data was collected from the website of Department of Statistics Malaysia, Official Portal. The data was taken for rubber and crops category. In order to run the analysis, the non-parametric approach was used, which is also knows as DEA (Data Envelopment Analysis). It is used to explore the efficient use of energy resources. The findings suggest that Rubber farms are the most technical efficient as compared to other farms. Further, the results show that there are many factors that counts and sums up the efficiency of the farm. Whilst studying the technical efficiency, this study finds that the soil and climate conditions contributes to the efficiency and productivity of the farms. Keywords: technical efficiency, energy resources, palm oil farms, crop farms, tea farms, rubber farms, Malaysian farms. JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.9195